(untitled) (Revista Nacional de Odontología, 2025)
Introduction: The relevance of this report lies in its detailed approach to the clinical management of a complex periapical lesion, illustrating the challenges and strategies employed to achieve a successful outcome. Furthermore, it provides updated information on surgical techniques, materials, and important considerations in the treatment of endodontic pathologies. Case report: A 62-year-old man was referred in June 2023 due to a radiolucent area at the apex of his right upper lateral incisor. After a thorough clinical history, involvement of two teeth was identified: a previously treated canine and an extensive lesion on the lateral incisor. Retreatment was performed on the canine, followed by disinfection and obturation. Purulent debris was identified in the lateral incisor, and the canal was disinfected and a temporary filling placed. After 15 days, the infection persisted, leading to a subsequent apicoectomy. The surgical procedure allowed for adequate visualization and access, followed by precise root-end instrumentation and retrograde sealing with Biodentine®. After suturing, the patient had a satisfactory recovery, with no symptoms at the follow-up visit in January 2024, confirming the success of the treatment. Discussion: The importance of ensuring adequate coronal sealing after endodontic treatment and the need to consider retreatment in cases of persistent symptoms are emphasized. Furthermore, the importance of detailed knowledge of root anatomy for treatment success is stressed. Periapical surgery is presented as a viable option in selected cases, highlighting the promising use of materials such as Biodentine® in apical surgery. The crucial importance of precise retrograde sealing and the consideration of anatomical contraindications for apical surgery are emphasized. It is also noted that most periapical lesions respond favorably to non-surgical treatment, and the key role of bioceramic cement in the repair of these lesions is highlighted. Conclusion: Apical surgery, although considered a last resort, has improved thanks to advances in techniques and materials. Its effectiveness as an alternative to tooth extraction is emphasized. However, longer follow-up periods are necessary to fully assess the treatment success.